EU development policy as a crisis-response tool? Prospects and challenges for linking the EU's COVID-19 response to the green transition - Svea Koch; Ina Friesen; Niels Keijzer (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This paper assesses the preferences of EU institutions and member states for the Union's development policy response to the COVID-19 pandemic. Addressing both the effects of climate change and biodiversity loss and the exacerbating socio-economic inequalities requires a response that links the short-term recovery of the pandemic with longer-term socio-ecological transformations. Our findings show that the EU and its member states have mainly responded to that challenge through Team Europe and Team Europe Initiatives. While these have contributed to defining a joint European response to the pandemic, the strong focus on climate and green transitions and the lack of connections to the broader SDG agenda as well as social and human development have created tensions between some member states and the EU. A key challenge ahead in further defining the European response to the pandemic is finding new strategic directions and operational means for bridging these differing priorities.
Keywords: 330